Respuesta :
There are several ways to confirm that the two expressions are equal. One method is to simply factor the first expression and see it you get a result equal to the second expression. An easier method is to set a value for x and substitute it to the two expressions. If the resulting value is that same, this means that the two expressions are equal.
Answer:
to calculate what Angelina wrote. =(x^-16)^2(x^2+16)
=(x^2)^2-2x^2*16+16^2
=(x^4-32x^2+256)(x-16)
=x^4x^2+x^2*16+(-32x^2)x^2+(-32x^2)*16+256x^2+256*16
=x^6-16x^4-256x^2+4096
can see that first term is x^6.
But for (x - 4)^8 expression, first term should be x^8.
So say that Angela’s solution is incorrect.
Step-by-step explanation: